Professionele benaderinge tot die versorging van die bejaarde - W.J. Kotzé (AOSIS, 1979)
There are few phenomena in the life of man which cause so many misconceptions and fallacies as the concept of aging. Probably the reason for this is to be found in the materialistic spirit of our times to which man is constantly exposed from the embryonic phase of his existence. Unless the members of the therapeutic team themselves believe in the meaning of life and in the unique, irreplaceable value of each human life, and, unless this belief is realised in their own personal lives and in relation to others, they will not be able to lead any other person to a meaningful life.